1999
DOI: 10.1523/jneurosci.19-16-06844.1999
|View full text |Cite
|
Sign up to set email alerts
|

Subtype-Dependence of NMDA Receptor Channel Open Probability

Abstract: NMDA receptor-mediated calcium transients play a critical role in synaptogenesis, synaptic plasticity, and excitotoxicity. NMDA receptors are heteromeric complexes of NR1A combined with NR2A, NR2B, NR2C, and/or NR2D subunits. The NR2 subunits determine a variety of electrophysiological and pharmacological properties of the NMDA receptor complex. In this report, we provide evidence for the first time that there is also a significant difference in peak channel open probability (P(o)) between NMDA receptors compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
164
3
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(187 citation statements)
references
References 43 publications
18
164
3
2
Order By: Relevance
“…1A). Using conventional mutagenesis to introduce point mutations at this site, we found that, depending on the side chain property, receptor gating can be bidirectionally manipulated, as assessed by the inhibition kinetics of MK-801, a selective NMDAR open-channel blocker classically used to index receptor channel P o (15,18,19) (SI Appendix, Fig. S1 A and B).…”
Section: Resultsmentioning
confidence: 99%
“…1A). Using conventional mutagenesis to introduce point mutations at this site, we found that, depending on the side chain property, receptor gating can be bidirectionally manipulated, as assessed by the inhibition kinetics of MK-801, a selective NMDAR open-channel blocker classically used to index receptor channel P o (15,18,19) (SI Appendix, Fig. S1 A and B).…”
Section: Resultsmentioning
confidence: 99%
“…Through the mGluRs, glutamate can modulate excitatory (AMPA and NMDA receptors) and inhibitory (GABA) signaling pathways, in addition to various ion channels, including many specific for potassium and calcium (9,21,46,52,86,100,101,175,179,186,213). Because these systems are inherently involved in the function and pathophysiology of CNS, drugs that modulate mGluRs can have multiple modulatory/therapeutic effects throughout the CNS.…”
Section: Introductionmentioning
confidence: 99%
“…The ATDs of glutamate receptors are known to be involved in receptor assembly and in controlling the open probability of the receptor (1)(2)(3). Specifically, receptors composed of GluN1-GluN2A subunits exhibit a higher channel open probability than those composed of GluN1-GluN2B subunits (4,5). This inherent difference in the open probabilities arises, to a large extent, from the ATDs, as switching the ATD of GluN2A with that of GluN2B results in a swap in the channel open probabilities, albeit not completely (2).…”
mentioning
confidence: 99%